Barcarena cidade-obra: cartografia de uma cidade entontecida - CARDOSO, Sebastião de Jesus (Universidade Federal do Pará, 2017)
This work composes on an artistic, aesthetic and critic reading about Barcarena. It looks for a comprehension of its urban area. It is divided into three moments: The Historical city, the image city and the aesthetic city, searching in a reading with Mumford, Argan, Guimarães, Lynch, Rossi, Deleuze, Guattari and Calvino, the way it is established in History. This reading shows how this city is today, at the same time that it is projected on a specific way to see it. Therefore, the idea of a cartography of its areas on an entontecida writing.